The taxation of corporate income in India - Ambirajan, S. (London : Asia Publishing House, 1964)
The aim of the book is to study the evolution, structure , administration, effects and future prospects of the taxation of corporation income in India in the context of the changing ideas and concepts that are influencing our tax policy.
Includes index.
Includes bibliographical references: p. 304-312.
gp 24/01/2019
Loans
Keywords: Corporations--Taxation.; Income tax; Economic policy; India